The properties of kashar cheese produced with added rennet casein - Abdullah Badem; Gürkan Uçar (Eurasian Journal of Veterinary Sciences)
Aim: It was aimed to investigate the changes in the chemical, microbiological and sensory properties of kashar cheese produced by adding different rates of rennet casein during ripening. Materials and Methods: Bovine milk (3,0% fat) was heated (37˚C), enzyme was added. After clotting, pressure and fermantation, emulsifying salts (0,1%), salt (1,5%) and rennet casein (%0-control, 0,5, 1,0, 1,5, 2,0) was added. Produced cheese at melting tank (65˚C, 5 min) was packaged and was ripened (8˚C, 90 days). In samples, dry matter was conducted with gravimetric, fat with Gerber, salt with Mohr and titration acidity with % lactic acidity. Total mesophilic aerobic bacteria, lactic acid bacteria, S.aureus, coliform bacteria, yeast-mould contents of the samples were examined. Sensory evaluation was performed by 7 panelists. One-way Anova test and Kruskal-Wallis H test was used for istatistically analysis. Results: Cheeses were ripened at 8˚C and were analyzed during the ripening period (90 days). pH value was found between 5,62-5,76, acidity 0,55-0,83L.a., drymatter 54,93-58,04%, salt 1,22-1,37%, salt in drymatter 2,21-2,45%, fat 23,67-25,33% and fat in drymatter 41,20-45,46%. Mean values were determined to TAMB 5,17-5,75 logcfu/g, LAB 5,49-6,98 logcfu/g, mould- yeast 3,66-4,88 logcfu/g. There was a significant difference (p<0,05) on titratable acidity and pH of the cheeses, but no difference (p> 0,05) was found on other criteria. Total scores were between 20,62-22,19 point at sensory evaluation. In the sensory analysis, 3rd group cheese in terms of external appearance and 2nd group cheese in terms of internal appearance statistically have significant difference (p <0,05). Conclusion: In the production of kashar cheese, it can be stated that production can be made and ripening can be achieved by adding rennet casein.